Normal phenotype and partial trisomy for the G positive region of chromosome 21. Issue 3 (June 1979) - Daniel, A
Abstract : A prenatally diagnosed male fetus and his mother, who was referred because of her advanced age, both carried an abnormal bisatellited chromosome 21 as an extra chromosome. The abnormal 21 was monocentric and the G negative band q22 and part of q21 had been deleted during formation. The phenotype of both the mother and child (at birth) was normal.